KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PAD DAN APBD - Candra Dian Etika, 09.05.52.0164; Setyowati, Widhy (Students Journal of Accounting and Banking, 2013)
This research is a research that analyzes the contribution of local taxes and levies on revenue and the Revenue and Expenditure (Budget) for the implementation of regional autonomy. This research use data of sekunder from documentation hit report of local tax, levies, revenue, and budget of year 2009-2012 at the Revenue Department of Finance and Asset Management District of Pati regency. Data analysis methiod used by writer kualitative method with the analysis of the growth, contribution and effectiveness. The population and sample in this research is data local taxes and levies in 2009-2012 on the Revenue Department of Finance and Asset Management District of Pati regency. The results showed that the local tax and levies contribution to the revenue at an average of 17.59% and 28.21% per year. While the contribution of local tax and levies to the budget in Pati regency with the ability to finance the expenditure at an average of 1.90% and 2.83% per year. The growth of local tax for four years of 24.96%. The effectiveness of local taxes averaged 115.08% per year, this means that the effectiveness has been very effective in the area of tax collection. While the growth of levies for four years of -2.28%. The effectiveness of local taxes averaged 103.26% per year, this means that the effectiveness has been very effective in the area of levies collection. Keywords: Local Taxes, Levies, Revenue, Revenue and Expenditure Budget